The Threat No More? Indonesian Atheists, Pancasila, and the Search for A Common Moral Ground - M Ali (Journal of Asian Social Science Research, 2023)
The fall of Soeharto's rule in 1998 marked the beginning of a new era in Indonesian democratization, allowing old and new voices in the public realm, including atheists who defined themselves as no less Indonesian and, more crucially, no less moral than the rest. Globalization and increasing access to information and communication technology facilitated this. This article analyses how and why Indonesian atheists have become more outspoken in recent years about their lack of religious belief and defence of their denial of the existence of any deity or gods in response to their upbringing, education, news about religious radicalism, liberalism, and scientific advancement. These atheists provide context for atheism in Indonesia. They also redefine Indonesia as a non-religious nation-state, despite the country's Muslim population and efforts and aspirations to bring it closer to an Islamic state or culture. In numerous official declarations and textbooks, Indonesia has historically been referred to as neither a theocracy nor a secular state. It is a Pancasila state. Indonesian atheists redefine the country as a whole by reinventing Pancasila and Bhineka Tunggal Ika. They are not opposed to collaboration and unity. Instead of sacred or religious principles, they emphasize humanity and morality as common values.